Contextual Bible Study Notes - Robinson, Peter (The expository times, 2007)
The article relates the Contextual Bible Study on the gospel of Luke 12:32-40 held at Saint Michael's Parish Church in Newcastle upon Tyne, England. It states that some of the participants doubted whether they would ever be ready to sell their wealth for the benefit of poor people to respond to the unexpected nature of God. The author mentions that the group realized that it is easier to give to the poor than to find God in the poor and that material things have no real value.